The Effect of Promotional Strategies on Purchase Decisions at Pondok Lesehan Waroeng Ridwan, Pagar Alam City - Yolanda Bella Agrilia; Zulaiha zulaiha (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
This study aims to determine whether there is an Influence of Promotional Strategy on Purchase Decisions and to find out how much Promotional Strategy Variables on Purchase Decisions. This study uses associative research with a quantitative approach. There are two variables used in this research, namely Promotion Strategy (X) and Purchase Decision (Y). This data collection was obtained through distributing questionnaires to consumers of Waroeng Ridwan Products in Pagar Alam City. The sample used in this study were 84 respondents using Simple Linear Statistical Analysis and Sampling techniques. The results of the Simple Linear Regression Analysis Test in this study indicate that the Promotion Strategy has a positive effect on Purchase Decisions can be seen from the Simple Regression Analysis, namely: Y = 25.740 + 0.235. Which is where the constant value of 25,740 the regression coefficient value of the Promotion Strategy has a positive influence, which means that if the Promotion Strategy increases by one unit, the Purchase Decision will increase by 0.235 units. Promotion strategy has a significant effect on purchasing decisions at Pondok Lesehan Waroeng Ridwan in Pagar Alam City which can be seen from the results of the t test where the significant value is 0.000, which means it is smaller than 0.05 so the hypothesis is accepted.